Weak decay constant of pseudoscalar mesons in a QCD-inspired model - Salcedo, L. A. M.; Melo, J.P.B.C. de [UNESP]; Hadjmichef, D.; Frederico, T. (Sociedade Brasileira de Física, 2004)
We show that a linear scaling between the weak decay constants of pseudoscalars and the vector meson masses is supported by the available experimental data. The decay constants scale as f m/f p = MV/Mr (f m decay constant and M V vector meson ground state mass). This simple form is justified within a renormalized lightfront QCD-inspired model for quark-antiquark bound states.